THE USE OF ONLINE DISCUSSIONS TO SUPPORT STUDENTS COGNITIVE ENGAGEMENT IN LANGUAGE LEARNING - Veranika, Fenny; Salam, Urai; ., Sumarni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstrak: Studi dengan metode deskriptif ini bertujuan untuk meneliti keterlibatan kognitif mahasiswa dari program studi Bahasa Inggris dalam berpartisipasi pada diskusi online di kelas TL-ICT I B. Data berasal dari transkrip komentar mahasiswa di dalam forum online. Murid-murid berkontribusi pada diskusi online dalam beberapa tingkatan kognitif yang akan mengarah kepada dua tingkatan terbesar yaitu keterlibatan kognitif tingkat tinggi dan keterlibatan kognitif tingkat rendah. Keterlibatan kognitif tingkat tinggi akan membawa mereka kepada pengolahan informasi yang lebih dalam seperti penjabaran konsep ataupun debat. Sedangkan keterlibatan kognitif tingkat rendah merupakan pengolahan informasi secara sangat sederhana. Analisis konten dilakukan pada enam episod diskusi yang digunakan sebagai sampel. Dalam analisis ini terdapat lima kategori seperti kategori pertanyaan, pernyataan yang terbagi menjadi enam tipe yang berbeda berdasarkan taksonomi Bloom, kategori refleksi, mentor, dan skafold. Hasil penelitian menunjukan bahwa mayoritas mahasiswa berkontribusi dengan keterlibatan kognitif tingkat rendah, hanya pemikiran sederhana dengan sedikit pemahaman terhadap topik yang didiskusikan. Ini dibuktikan dari pengklasifikasian komentar mahasiswa yang terpusat pada kategori pernyataan tipe I (Responding) dan kategori pernyataan tingkat II (Informative). Kata Kunci: Diskusi online, Keterlibatan Kognitif Abstract: This descriptive study aims to investigate the cognitive engagement of English students in asynchronous online discussion of class TL-ICT I B. The data were derived from transcripts of students postings. Students contributed in online discussions in some levels of cognitive that lead to two broad levels engagement namely high level of cognitive engagement and lower level of cognitive engagement. High level of cognitive engagement will lead to deeper levels of information processing which are associated with elaborating concepts and debating or negotiating meaning. In the contrary, the low level of cognitive engagement refers to surface level of information proccessing. Using a coding rubric, The Analytical Framework for Cognitive Engagement in Discussion, content analysis was conducted on six episodes of the discussions as sample. This rubric consists of five categories such as question, statements divided into six different types based on Taxonomy Bloom, reflection, mentoring, and scaffolding. The findings showed that majority of students engaged with lower level of cognitive engagement, merely superficial thinking with a little understanding toward the issues. It was evidenced in the findings that contributions exhibited by the students centered on statement type I (Responding) and statement type II (Informative). Key words: Cognitive engagement, Online discussion